Peran Qana'ah Dalam Peningkatan Kepercayaan Diri dan Rasa Syukur Mahasiswa - Syakira Annisa Salsabila (PT Anugerah Literasi Indomedia, 2025)
This study aims to examine the role of qana’ah in enhancing students’ self-confidence and gratitude, as well as its implications for academic and social life. The study employs a qualitative approach using a library research method by analyzing relevant Islamic and psychological literature. The findings indicate that qana’ah is a spiritual value that functions as a psychological foundation in developing self-acceptance, emotional regulation, and mental balance among university students. Qana’ah contributes to the formation of stable self-confidence that is not solely dependent on external validation. In addition, it fosters sustainable gratitude by helping students recognize and appreciate life’s blessings in various circumstances. The implications of qana’ah are reflected in improved learning motivation, academic stress management, academic integrity, and the quality of students’ social relationships. This study emphasizes the importance of integrating the value of qana’ah into higher education as an effort to strengthen character development and students’ psychological well-being. Penelitian ini bertujuan untuk mengkaji peran qana’ah dalam peningkatan kepercayaan diri dan rasa syukur mahasiswa serta implikasinya terhadap kehidupan akademik dan sosial. Penelitian menggunakan pendekatan kualitatif dengan metode library research melalui analisis literatur keislaman dan psikologi yang relevan. Hasil kajian menunjukkan bahwa qana’ah merupakan nilai spiritual yang berperan sebagai fondasi psikologis dalam membentuk penerimaan diri, pengendalian emosi, dan keseimbangan mental mahasiswa. Qana’ah berkontribusi terhadap penguatan kepercayaan diri yang stabil karena tidak bergantung pada validasi eksternal semata. Selain itu, qana’ah juga menumbuhkan rasa syukur yang berkelanjutan dengan membantu mahasiswa menyadari dan menghargai nikmat dalam berbagai kondisi kehidupan. Implikasi qana’ah terlihat pada meningkatnya motivasi belajar, manajemen stres akademik, etika akademik, serta kualitas hubungan sosial mahasiswa. Penelitian ini menegaskan pentingnya integrasi nilai qana’ah dalam pendidikan tinggi sebagai upaya pembinaan karakter dan kesejahteraan psikologis mahasiswa.